Optimisation du procédé de soudage par résistance électrique dans l’industrie automobile - Inssaf BEGHENNA; Meriem NESSAIB (My University, 2025)
In the automotive industry, reducing vehicle weight is a key goal to lower fuel consumption. This encourages manufacturers to use stronger but thinner steels. To prevent corrosion, these steel sheets are coated with various protective layers depending on their application. ArcelorMittal, a major steel supplier for the automotive sector, develops new products that must be tested before being offered to customers, especially to ensure they can be properly welded. The most commonly used technique for assembling car bodies (known as "body-in-white") is resistance spot welding, where an electric current melts the sheets to bond them. However, when the sheets differ greatly in thickness or material (a so-called “dissimilar” assembly), problems may arise—especially if one sheet is very thin, as the weld might not hold it securely. This thesis focuses on studying such a welding configuration with an ultra-thin steel sheet (less than 0.6 mm), aiming to understand how the weld forms, which parameters affect its strength, and how to improve the process to ensure both a reliable and lightweight assembly. ------------------------------------------------------------------------- : في صناعة السيارات، يُعتبر تقليل وزن المركبات هدفًا رئيسيًا لتقليل استهلاك الوقود. وهذا يدفع الشركات المصنعة إلى استخدام أنواع من الفولاذ أكثر مقاومة ولكن بألواح أرق. ولحمايتها من التآكل، تُغطى هذه الصفائح الفولاذية بطبقات واقية مختلفة حسب استخدامها. تقوم شركة ArcelorMittal، وهي مورد رئيسي للفولاذ في قطاع السيارات، بتطوير منتجات جديدة يجب اختبارها قبل عرضها على العملاء، خاصةً لضمان إمكانية لحامها بشكل جيد. تُعد تقنية اللحام بالنقطة (Resistance Spot Welding) الطريقة الأكثر استخدامًا في تجميع هياكل السيارات (المعروفة باسم "الهيكل الأبيض"). حيث يستخدم تيار كهربائي لإذابة الصفائح ولحمها معًا. لكن عند استخدام صفائح تختلف كثيرًا في السماكة أو نوع المادة (ما يسمى بالتجميع غير المتماثل)، قد تحدث مشاكل، خصوصًا إذا كانت إحدى الصفائح رقيقة جدًا، إذ قد لا تثبتها اللحمة جيدًا. تركز هذه الأطروحة على دراسة هذا النوع من اللحام باستخدام صفيحة فولاذية رفيعة جدًا (أقل من 0.6 مم)، بهدف فهم كيفية تكوّن اللحام، والعوامل التي تؤثر على متانته، واقتراح حلول لتحسين العملية وضمان تجميع موثوق وخفيف الوزن. ------------------------------------------------------------------------- In the automotive industry, reducing vehicle weight is a key goal to lower fuel consumption. This encourages manufacturers to use stronger but thinner steels. To prevent corrosion, these steel sheets are coated with various protective layers depending on their application. ArcelorMittal, a major steel supplier for the automotive sector, develops new products that must be tested before being offered to customers, especially to ensure they can be properly welded. The most commonly used technique for assembling car bodies (known as "body-in-white") is resistance spot welding, where an electric current melts the sheets to bond them. However, when the sheets differ greatly in thickness or material (a so-called “dissimilar” assembly), problems may arise—especially if one sheet is very thin, as the weld might not hold it securely. This thesis focuses on studying such a welding configuration with an ultra-thin steel sheet (less than 0.6 mm), aiming to understand how the weld forms, which parameters affect its strength, and how to improve the process to ensure both a reliable and lightweight assembly.
Keywords: Resistance spot welding; Dissimilar assembly; Thin sheet; Joule effect; Numerical simulation; اللحام بالمقاومة النقطية، التجميع غير المتماثل، الصفيحة الرقيقة، تأثير جول، المحاكاة العددية; Soudage par résistance par point; Assemblage dissymétrique; Tôle fine; Effet Joule; Simulation numérique.